(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article investigates the methodological importance of advanced foreign and national pedagogical practices in the development of students’ core competencies in robotics education. As robotics becomes a critical component of modern STEM curricula, understanding and adapting international best practices alongside national educational innovations is essential for shaping a competitive and technologically skilled generation. The research examines leading models of robotics education from technologically advanced countries, such as Japan, South Korea, the United States, and Germany, and compares them with the emerging national practices in Uzbekistan. It outlines how these practices can inform methodological preparation, curriculum design, and assessment strategies to foster algorithmic reasoning, engineering design skills, and digital literacy. The study employs a comparative and analytical research methodology supported by a pedagogical experiment in selected educational institutions. Findings reveal that the integration of foreign best practices with national educational contexts enhances both teacher capacity and student learning outcomes in robotics.